Polytechnic science lecturers’ intention to use ICT as a tool in northeast Nigeria: a smart PLS approach - Yohanna, G.; Md Yunos, Jailani; Mohamad, Marlina; Ruth, J. Y. (Universiti Putra Malaysia Press, 2017)
This study appraises the intention of educators to use computer technology for teaching and learning in Northeastern Nigeria, a region comprising Adamawa, Bauchi, Borno, Gombe, Taraba and the Yobe States. Although the Nigerian government has provided computers for teaching and learning, they are underutilised. A survey was conducted to validate items recorded in past studies. The Technology Acceptance Model (TAM) was employed as a theoretical framework. The Bootstrapping Algorithm with SmartPLS was applied for modelling interaction with 269 subjects from the targeted populations of 715 science lecturers from Northeast Nigeria. Several studies affirmed a significant influence of perception of usefulness and perception on ease-of-use on attitude towards technology acceptance and were validated in different behavioural intention to use. Perceived usefulness and ease-of-use explain individual attitude and directly influence intention. This study investigates influence attributes of the Technology Acceptance Model (TAM) towards use of the computer as a teaching aid among lecturers in Nigeria. Constructs based on TAM (perceived usefulness, ease-of-use and attitude on behavioural intention to use a computer) also supported the impact of perceived ease-of-use on perceived usefulness and towards the lecturers’ attitude. Overall, variance explained indicated 40%. The result verifies TAM as robust and can be applied within different cultures. This implies that teaching in polytechnics and other institutions of higher learning can be improved if computers and training to facilitate ease-of-use are provided for lecturers.